Pembinaan Pengawas Sekolah dalam Upaya untuk Meningkatkan Kompetensi Kewirausahaan Kepala Sekolah di Gugus Kusuma Bangsa Kecamatan Sawangan Kabupaten Magelang - Lestari Munhayati (Universitas Sebelas Maret, 2020)
Abstract. The purpose of this study was to determine the increase in the entrepreneurial competence of school principals in the Kusuma Bangsa Cluster, Sawangan District, Magelang District, Odd Semester, 2018/2019 Academic Year through the guidance of school supervisors. This type of research is a study that uses a school action research (PTS) design with a qualitative approach. The subjects of this study were 10 school principals in the Kusuma Bangsa Cluster, Sawangan District, Magelang Regency. The main data were obtained from theclass teacher. Data collection methods by interview, observation, and documentation methods. The results of this research were able to improve the entrepreneurial competence of school principals in the Kusuma Bangsa Cluster, Sawangan District, Magelang Regency, both in quality and quantity. Before giving action in the form of school supervisor coaching, the entrepreneurial competence of the School Principal in the Kusuma Bangsa Cluster, Sawangan District, Magelang District only reached a percentage of 60.50% (there were 4 Principals in the poor category, 5 Principals in the good category and 1 School Principal included in the very good category), after being given the action there was an increase in cycle I of 70.50% (there were 2 Principals in the poor category, 6 Principals were in the good category and 2Principals were in the very good category) and in cycle II increased to 81.50% (there were 5 Principals in the good category and 5 Principals in the very good category).